Model‐informed approach to support pediatric dosing for the pan‐PI3K inhibitor copanlisib in children and adolescents with relapsed/refractory solid tumors - Peter N. Morcos; Jan Schlender; Rolf Burghaus; Jonathan Moss; Adam Lloyd; Barrett H. Childs; Margaret E. Macy; Joel M. Reid; John Chung; Dirk Garmann (Wiley, 2023)
Abstract Copanlisib is an intravenously administered phosphatidylinositol 3‐kinase (PI3K) inhibitor which was investigated in pediatric patients with relapsed/refractory solid tumors. A model‐informed approach was undertaken to support and confirm an empirically selected starting dose of 28 mg/m2 for pediatric patients ≥1 year old, corresponding to 80% of the adult recommended dose adjusted for body surface area. An adult physiologically based pharmacokinetic (PBPK) model was initially established using copanlisib physicochemical and disposition properties and clinical pharmacokinetics (PK) data and was shown to adequately capture clinical PK across a range of copanlisib doses in adult cancer patients. The adult PBPK model was then extended to the pediatric population through incorporation of age‐dependent anatomical and physiological changes and used to simulate copanlisib exposures in pediatric cancer patient age groups. The pediatric PBPK model predicted that the copanlisib 28 mg/m2 dose would achieve similar copanlisib exposures across pediatric ages when compared with historical adult exposures following the approved copanlisib 60 mg dose administered on Days 1, 8, and 15 of a 28‐day cycle. Clinical PK were collected from a phase I study in pediatric patients with relapsed/refractory solid tumors (aged ≥4 years). An established adult population PK model was extended to incorporate an allometrically‐scaled effect of body surface area and confirmed that the copanlisib maximum tolerated dose of 28 mg/m2 was appropriate to achieve uniform copanlisib exposures across the investigated pediatric age range and consistent exposures to historical data in adult cancer patients. The model‐informed approach successfully supported and confirmed the copanlisib pediatric dose recommendation.